Muscle protein synthesis responses following aerobic-based exercise or high-intensity interval training with or without protein ingestion: a systematic review - Bagheri, R.; Robinson, I.; Moradi, S.; Purcell, J.; Schwab, E.; Silva, T.; Baker, B.; Camera, D. M. (Sports Medicine, 2022)
Background: Systematic investigation of muscle protein synthesis (MPS) responses with or without protein ingestion has been largely limited to resistance training. Objective: This systematic review determined the capacity for aerobic-based exercise or high-intensity interval training (HIIT) to stimulate post-exercise rates of MPS and whether protein ingestion further significantly increases MPS compared with placebo. Methods: Three separate models analysed rates of either mixed, myofibrillar, sarcoplasmic, or mitochondrial protein synthesis (PS) following aerobic-based exercise or HIIT: Model 1 (n = 9 studies), no protein ingestion; Model 2 (n = 7 studies), peri-exercise protein ingestion with no placebo comparison; Model 3 (n = 14 studies), peri-exercise protein ingestion with placebo comparison. Results: Eight of nine studies and all seven studies in Models 1 and 2, respectively, demonstrated significant post-exercise increases in either mixed or a specific muscle protein pool. Model 3 observed significantly greater MPS responses with protein compared with placebo in either mixed or a specific muscle fraction in 7 of 14 studies. Seven studies showed no difference in MPS between protein and placebo, while three studies reported no significant increases in mitochondrial PS with protein compared with placebo. Conclusion: Most studies reporting significant increases in MPS were confined to mixed and myofibrillar PS that may facilitate power generating capacity of working skeletal muscle with aerobic-based exercise and HIIT. Only three of eight studies demonstrated significant increases in mitochondrial PS post-exercise, with no further benefits of protein ingestion. This lack of change may be explained by the acute analysis window in most studies and apparent latency in exercise-induced stimulation of mitochondrial PS.